Business cycle dating and forecasting with real-time Swiss GDP data - Christian Glocker; Philipp Wegmüller (Austrian Institute of Economic Research (WIFO), 2017)
We develop a small-scale dynamic factor model for the Swiss economy based on an appropriately selected set of indicators. The resulting business cycle factor is in striking accordance with historical Swiss business cycle fluctuations. Our proposed model demonstrates a remarkable performance in short-term and medium-term forecasting. Using real-time GDP data since 2004, the model successfully anticipates the downturn of 2008-09 and responds in a timely manner to the recent sudden drop following the removal of the Swiss Franc lower bound. In a Markov-switching extension, we propose that our model could be used for Swiss recession dating. Our model does not indicate a regime-switch following the removal of the Swiss Franc lower bound.
Keywords: C32; C53; E37; 330; Dynamic Factor Model; Nowcasting; Real-Time Data; Markov-Switching